CHALLENGES AMONG CANCER PATIENTS THAT MAY INFLUENCE RECOVERY OUTCOMES IN PALLIATIVE CARE UNITS IN NAIROBI AND NYERI COUNTIES - Wang'ombe, Joyce; Kathungu, Beatrice (Global Journal of Health Sciences, 2021)
Purpose: This study sought to establish challenges among cancer patients that may influence recovery outcomes in palliative care units in Nairobi and Nyeri Counties. Methodology: The study adopted a correlation research design. The target population were the cancer patients, attending treatment at the three palliative care units in Nairobi and Nyeri Counties. Systematic random sampling technique was used in the study to obtain a sample of 96 participants. Semi structured questionnaires were used to collect data. Data was analyzed using both descriptive and inferential statistics, namely Pearson Moment Correlation Coefficient(r). Findings: Result showed that, majority of the respondents indicated participating in the programs available at the palliative care institutions, which included; group psychotherapy (91.7%), spiritual support (91.7%) and programs on coping skills (91.7). Others (22.6%) participated in programs such as performing chorals, knitting and board games. The results also showed that 82.1% and 78.6% of the respondents noted that they experienced challenges of being isolated and lacking finances respectively. 50% of the respondents had a challenge in coping with the condition, while 2.4% experienced challenges in adhering to drugs .These findings were not unusual considering that most of the patients were newly diagnosed with cancer and for some respondent's metastasis had set in. Unique contribution to theory, practice and policy Patients facing challenges receiving palliative care could adopt group psychotherapy, including cognitive-behavioral, informational, non-behavioral, social support, and using unusual treatments such as music and art therapy to curb cancer. Administrators and medical staff in the palliative care units should create awareness and encourage the attending patients to source for a health insurance cover e.g. National Health Insurance Fund (NHIF) to cater for the cancer disease both outpatient and incase of hospitalization. This will ease the financial burden of cancer on the patient, family and community.